The Implementation of Management in the Child Friendly School Program at SD Negeri 05 Bojongbata, Pemalang Regency - Wijayanti, Dian; Kusumaningsih, Widya; Soedjono, Soedjono (Jayapangus Press, 2025)
This study aims to describe the implementation of management in the Child-Friendly School (Sekolah Ramah Anak/SRA) program at SDN 05 Bojongbata, Pemalang Regency. The SRA program is designed to foster an environment that supports the optimal fulfillment of children's rights through inclusivity and protection. Employing a qualitative descriptive phenomenological approach, the research utilized observations, in-depth interviews, and documentation to analyze management functions: planning, organizing, implementation, and supervision. The findings show that SRA program management at the school is systematic and participatory. Planning involves setting clear objectives, designing activities, developing implementation strategies, and assessing challenges and resources. Organizing is realized through the formation of an implementation team with structured task allocation and routine coordination. Implementation benefits from principal leadership, clear directives, and ongoing motivation to encourage active participation from all school members. Supervision is carried out via regular evaluation and follow-up based on established success criteria. Key success factors include stakeholder engagement, adequate facilities, and collaboration with external partners such as health centers. Nevertheless, challenges remain, particularly regarding limited human resources and funding, which must be addressed to ensure program sustainability. This study contributes both scientifically and practically by highlighting the pivotal role of effective, participatory school management especially in planning, leadership, and stakeholder collaboration as the foundation for optimizing and sustaining Child-Friendly School initiatives.